Embedded System Training for Enhancing School Security and Technological Literacy at SMA Negeri 10 Bandar Lampung - Susanto, Try; Putri, Novia Utami; Jayadi, Akhmad; Bani, Marsi; Puspaningrum, Ajeng Savitri (MEKONGGA: Jurnal Pengabdian Masyarakat, 2025)
The main problem faced by the partner, SMA Negeri 10 Bandar Lampung, was the absence of a technology-based security system and the low level of technological literacy among students. To address these issues, a community service program was conducted through training and implementation of an embedded system focused on designing and applying a microcontroller-based doorlock security device. The activity employed several stages, including observation, interactive training, hands-on practice, and evaluation. The program was carried out over three months with five visits, involving 30 participants consisting of teachers and students. The results showed a significant improvement in participants’ knowledge, with an average increase of 51.26%, and an active participation rate reaching 95%. Furthermore, the developed security device functioned properly and was successfully implemented in one of the school’s rooms. This activity not only enhanced school security but also fostered awareness of the importance of technology utilization in education, supporting the development of digital literacy and 21st-century skills among the participants.